The Church and the Two Nations in Late Medieval Armagh (Presidential Address) - Watt, J. A. (Studies in church history, 1989)
Perhaps I can best introduce my paper, explain its nature and state my objective in writing it, by describing it as another step towards completing the second part of a study of which my book The Church and the Two Nations in Medieval Ireland was the first part.’ The study which concluded with the Statute of Kilkenny of 1366 needs extending chronologically by at least a century. More importantly, the nature of the analysis itself needs to be deepened. The ‘Two Nations’ book began with asking a fairly simple and limited question: what was the relationship of the ecclesiastical and civil powers within the English-settled parts of Ireland—in short, English law and the Irish Church. But it ended raising a more complex and more fundamental question about the overall effects on the Church of the establishment in Ireland of an English colony which was not coterminous with the country as a whole and whose strength and influence declined in the later middle ages. There may have been a more or less satisfactory answer in the book to the restricted question. There was, at best, no more than a tentative beginning to an answer to the more fundamental one.